PERANAN WANITA DALAM MENINGKATKAN PENDAPATAN KELUARGA DENGAN MEMANFAATKAN HUTAN MANGROVE (Wanatani mangrove) DI DESA SEI NAGALAWAN KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Reni Dewina Purba; Juliana Br Simbolon; Rafael Remit Winardi (JURNAL AGROTEKNOSAINS, 2020)
The aim of study is to identify and analyse the role of women in improving their incomes by taking advantage of mangrove forest (Wanatani mangrove) in economic activities in Sei Naga Lawan village, Perbaungan sub district, Serdang bedagai regency among these are the age of farm women (x1), income of farm women (x2), farm women’s land area (x3), marital status of test (x4), experience level (x5) analyze the revenue afforded the womenworking over mangrove accounts in their contributions to his family revenues. The result of the correlation test, the influential factor in booting farm women’s incomes is based on linear regression to variabel influences in farm women’s incomes. Based on the first hypothes put by researches, the variabels of agricultural stock to mangrove forest are influenced (x1 and x5), which account for a significant and redlified significance of 0.05 (0.016). Thus, it can be inferred that the rate of peaset women’s wages have a bearing on income. The insignificant facts raised by researches show that variabel land area (x3) and subsequent variabels show that marital status (x4) and so do variable rates of experience (x5) are incalculable to the incomes of mangrove farm women.